Gastric Antral Webs: Anatomical Variants and Appropriate Endotherapy - Varadarajulu, Hema V.; Mohanasundaram, Kavitha (Journal of Digestive Endoscopy, 2020)
We report the case of a 65-year-old patient with rheumatoid arthritis presenting with dyspeptic symptoms. Upper gastrointestinal (UGI) endoscopy revealed a gastric antral web, which was confirmed by UGI series. The presence of webs in the gastrointestinal tract, excluding the esophagus, is a rarity. Here, we highlight the anatomical variations in antral webs and endoscopic diagnosis, which ultimately influence the type of endotherapy.
Keywords: gastric antral web; dyspepsia; gastric outlet obstruction